MEMPERTEGAS KEMBALI ARAH PEMBELAJARAN BAHASA ARAB (Perspektif Budaya Terhadap Tradisi Belajar Bahasa Arab di Indonesia) (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2015)
The historical development of Arabic language in Indonesia can not beseparated from the spread of Islam which is the most dominant followed byIndonesian society itself. This has an impact on the development of Arabiclearning today, that look is still far from the expected. It seems that view ofthe cultural and religious patterns of Indonesia in the early 19th centurythat are still at the level of mythic and theological, less positive effect onthe future of Arabic learning in today’s contemporary world. How is therelationship between religion and its influence on the development of theArabic language, especially in Indonesia will be described in this paper. Byusing the theory of van Peursen culture and Comte as theoretical analysis,author tries to find a possible alternative solutions of some negative effectsin the mythic dimensions of the such view, by emphasizing the positiveaspects.